The effect of a psychological climate for creativity on job satisfaction and work performance - Wong, Foong Yee; Leong, Sai Pink; Lee, Mervyn Chia Sern (Faculty of Economics and Management, Universiti Putra Malaysia, 2014)
The organisational climate for creativity has been widely acknowledged to influence various work outcomes such as employee innovation and productivity. Researches carried out on the creative climate in Malaysia have up till now, confirmed the notion. However, as far as the Malaysian context is concerned, the effect of a creative work environment on employee job satisfaction and work performance level has yet to be explored. As such, this study aims to investigate the effects of a psychological climate for creativity on job satisfaction and work performance. Additionally, this study seeks to establish the role of job satisfaction as a mediator on the relationship between organisational climate and work performance. The results from a sample of 118 electrical engineers working only within the area of the Klang Valley suggest that all variable relationships were positively and significantly correlated: Job satisfaction - Work performance, Psychological climate for creativity - Job satisfaction and Psychological climate for creativity - Work performance. Moreover, job satisfaction was found to mediate between the psychological climate for creativity and work performance when an analysis was carried out on three separate regressions.